Avaliação do Projeto São José: discurso e prática nos subprojetos de mecanização no Município de Jardim - CE - Santos, Maria do Socorro (2010)
The phenomenon of participation in public policy, begins to take shape in the 1950s, when installed in Brazil, the consumer trend and practices of community development that initially appear as a means of effecting the policy of modernization. Manifesting itself more strongly from the 1960s. As if that were showing the contradictions of the housing areas were formed in space for popular mobilization and organization, to meet consumption requirements formulated by industrialization. Based on this understanding this study focused on the purpose of evaluating the participatory strategy Project São José of Agricultural Mechanization in the city of Jardim in the State of Ceará. As such, it posed the question: The project includes São José in the process of formulating and implementing the concepts of holding referred to in your strategy? In this sense, through a qualitative approach, and the use of quantitative-oriented and quality was initiated research work which was conducted in eight local farmers. The research was conducted with 113 farm families and 15 staff representatives from institutions / entities. The evaluation result suggests that participation in the São José Project is not effective in all its stages, a fact only identified at the time of release of funds by signing the agreement (Association and State). Yet still indicates limitations with regard to the degree of awareness, social organization and training of persons involved in the program.